Tindak Pidana Kuasa Penuh Dalam Perjanjian Fidusia Pembiayaan Kendaraan Bermotor - Maysarah Maysarah (Iuris Studia: Jurnal Kajian Hukum, 2020)
The agreement in the Civil Code has several legal requirements to be precise in Article 1320 of the Civil Code. For the validity of an agreement, 4 conditions are needed, namely the existence of an agreement, skill, the existence of certain things that have been agreed upon and the existence of a lawful cause. The first and second terms are called subjective conditions, because with regard to the subjects who make the agreement, if the agreement made is not in accordance with the first and second conditions, the agreement can be declared null and void. Meanwhile, the third and fourth terms are called objective conditions because they relate to the object in the agreement. If the agreement made does not meet the third and fourth conditions, the agreement is null and void. This writing uses normative juridical legal research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of social symptoms regarding the role of psychiatrists in proving psychological violence in criminal acts of domestic violence. Sources of research data are primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. The regulation regarding this Fiduciary Guarantee is regulated in Law NO. 42 of 1999 concerning the Fiduciary Guarantee. The presence of Law no. 42 of 1999 in essence only formalizes Normative rules from legal practice that have been enforced by Jurisprudence which are then encouraged again by the emergence of the Fiduciary Guarantee in Article 15 of Law No. 4 of 1992 concerning housing and settlements which stipulates that a house built on land owned by another party can be burdened with a Fiduciary Guarantee, as well as in Law no. 16 of 1985 concerning Flats, where it is found that the property rights over units of Flats can be used as collateral for debt by means of Fiduciary. Basically the full power of the fiduciary agreement has violated the rules of the validity of the agreement in Article 1320 of the Civil Code, then from that full power a criminal act can occur